Spatio-temporal analysis of bovine theileriosis (Theileria parva) in Zimbabwe from 1995 to 2018 - Marufu, Munyaradzi Christopher (University of Pretoria, 2024)
Mini Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2020.